Clean Intermittent Catheterization in Children under 12 Years Does Not Have a Negative Impact on Long-Term Graft Survival following Pediatric Kidney Transplantation - Marcou, Marios; Galiano, Matthias; Tzschoppe, Anja; Sauerstein, Katja; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hirsch-Koch, Karin; Apel, Hendrik (Journal of Clinical Medicine, 2024)
Background: Congenital anomalies of the kidneys and urinary tract (CAKUTs) are one of the most prevalent primary causes of end-stage renal disease (ESRD) in young children, and approximately one-third of these children present with lower urinary tract dysfunction (LUTD). Many children with LUTD require therapy with clean intermittent catheterization (CIC). CIC commonly leads to bacteriuria, and considerations have arisen regarding whether CIC in immunosuppressed children is safe or whether repeated febrile urinary tract infections (UTIs) may lead to the deterioration of kidney graft function. Material and Methods: We retrospectively reviewed all cases of primary kidney transplantation performed in our center between 2001 and 2020 in recipients aged less than twelve years. The number of episodes of febrile UTIs as well as the long-term kidney graft survival of children undergoing CIC were compared to those of children with urological causes of ESRD not undergoing CIC, as well as to those of children with nonurological causes of ESRD. Results: Following successful kidney transplantation in 41 children, CIC was needed in 8 of these patients. These 8 children undergoing CIC had significantly more episodes of febrile UTIs than did the 18 children with a nonurological cause of ESRD (p = 0.04) but not the 15 children with a urological cause of ESRD who did not need to undergo CIC (p = 0.19). Despite being associated with a higher rate of febrile UTIs, CIC was not identified as a risk factor for long-term kidney graft survival, and long-term graft survival did not significantly differ between the three groups at a median follow-up of 124 months. Conclusions: Our study demonstrates that, under regular medical care, CIC following pediatric transplantation is safe and is not associated with a higher rate of long-term graft loss.
CRIS-Team Scopus Importer:2024-01-19
Keywords: CAKUT; catheterization; child; kidney transplantation; LUTD